Temperature and time dependence of manganese evaporation in liquid steels. Multiphysics modelling and experimental confrontation. (December 2022) - Klapczynski, Vincent; Courtois, Mickael; Meillour, Ronan; Bertrand, Emmanuel; Maux, Dylan Le; Carin, Muriel; Pierre, Thomas; Masson, Philippe Le; Paillard, Pascal
Abstract: Unintended evaporation of additive elements can be observed on alloys during processes involving high temperatures and fusion. Indeed, welding, casting and additive manufacturing of steels lead to temperatures sufficiently high to start the evaporation of some low boiling point element such as manganese. In this paper, both experimental and numerical approaches are developed to study and quantify this phenomenon. Experimentally, an ex-situ aerodynamic levitation apparatus is employed to apply varying temperatures or durations at liquid state to a 304L steel sample. These experiments are represented numerically with a multiphysics model solving heat transfer, fluid flow and evolution of concentration of manganese dynamically. Equations chosen to represent this poorly studied phenomena are presented and compared to experiments. A comparison highlights a good accuracy of the proposed model. This precision increases particularly when the melting duration is high. Order of magnitude of evaporation phenomena is precisely quantified with time and temperature dependencies. Graphical abstract: Image, graphical abstract